Comparison of Tax Laws for Micro, Small, and Medium Enterprises in Developing Countries - Widjaja, Gunawan (Journal of Ecohumanism, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of economies in many developing countries. They played a vital role in job creation and income distribution. Given the importance of SMEs in increasing economic inclusion and reducing poverty, governments in developing countries often implement tax policies designed to support SMEs’ growth and sustainability. Moreover, education and tax support are important efforts in improving MSMEs’ understanding of their tax obligations, with tax ownership often associated with access to broader benefits, including financing. Despite variations in implementation, the study stresses the importance of continuous dialogue between governments and MSME owners, as well as the need for a flexible and responsive approach to MSME needs in developing countries. In conclusion, this research contributes to a better understanding of how developing countries can design effective tax policies to support the development of MSMEs, ultimately contributing to more inclusive economic growth.